Anguilla bengalensis ... - Esmaeili, Hamid Reza; Hamidan, Neshat (Zenodo, 2023)
1. Anguilla bengalensis (Gray, 1831) ―Mottled Eel/ African or Indian Mottled Eel― Native Taxonomy. Original description: Muraena bengalensis Gray, 1831:no page number, Pl. 95 (fig. 5) [India; No types known]. Synonyms: Anguilla arracana McClelland, 1844; Anguilla brevirostris McClelland, 1844; Anguilla elphinstonei Sykes, 1839; Anguilla variegata McClelland, 1844. Status in the Arabian Peninsula. First report from the Arabian Peninsula by Attaala & Salim Rubaia (2005); confirmed by Freyhof et al . (2020:113), and Heemstra et al. (2022:84). General distribution and Habitat. Indian Ocean and adjacent freshwater habitats: South Africa north to Kenya, east to Malaysia, north to Nepal. Freshwater, brackish, marine. Distribution in the Arabian Peninsula. Recorded from Yemen in Wadis Hajr and Masila (Attaala & Salim Rubaia 2005; Freyhof et al. 2020). Economic importance. No commercial importance. Conservation. Near Threatened (NT). Remarks. It has been recognised as A. bengalensis ... : Published as part of Esmaeili, Hamid Reza & Hamidan, Neshat, 2023, Inland fishes of the Arabian Peninsula: Review and a revised checklist, pp. 201-226 in Zootaxa 5330 (2) on pages 205-206, DOI: 10.11646/zootaxa.5330.2.2, http://zenodo.org/record/8249316 ...